2012
DOI: 10.4103/2230-8210.95714
|View full text |Cite
|
Sign up to set email alerts
|

Dermopathy of Graves′ disease: Clinico-pathological correlation

Abstract: Dermopathy of Graves’ disease is a classical, but uncommon extrathyroidal manifestation of Graves’ disease. The images of a typical case of dermopathy of Graves’ disease are presented along with clinico-pathological correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In our study, insulin resistance was identified as HOMA-IR ≥ 2 and insulin sensitivity was identified by HOMA-IR < 2. This was in line with earlier studies by Sinha et al [ 16 ] and Ray et al [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, insulin resistance was identified as HOMA-IR ≥ 2 and insulin sensitivity was identified by HOMA-IR < 2. This was in line with earlier studies by Sinha et al [ 16 ] and Ray et al [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…A recent study by Ray et al has showed TG/HDL-C and TC/HDL-C as insulin resistance markers in the ACS patients with impaired fasting glucose [ 17 ]. Our study included ACS patients who had normal glycemic levels and we also included Lp(a), along with the lipid profile parameters in the lipid ratios for prediction of insulin resistance, as south Indians are genetically known to have higher preponderance for CAD and higher Lp(a) levels and high incidence of central obesity and insulin resistance [ 23 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Graves’ dermopathy is an extra-thyroidal manifestation exclusively found in GD patients. Dermopathy develops in the presence of high TSHR antibody levels and is, with a frequency of 15%, a less common extra-thyroidal manifestation of GD ( 118 ). The main localization is pretibial and is associated with acropachy (digital clubbing, swelling of digits and toes, and periosteal reaction of extremity bones) in 20% of patients.…”
Section: Anti-thyroid Antibody Types: the Key To The Diagnosismentioning
confidence: 99%
“…Almost all cases are preceded by severe thyroid associated orbitopathy (TAO) 2. However, PTM is rarely seen in Asians and this has been attributed to reduced severity of TAO, lower prevalence rates of smoking and ethnicity 3. Our patient did not have active TAO but had severe nodular PTM.…”
Section: Discussionmentioning
confidence: 74%